2003
DOI: 10.1080/1356182031000081768
|View full text |Cite
|
Sign up to set email alerts
|

Student attitudes to undergraduate interprofessional education

Abstract: Interprofessional education in health care has been the focus of increasing attention in recent years. However, there is still great debate about when and how to introduce it in undergraduate studies. St George's Hospital Medical School with the Joint Faculty of Health Care Sciences of Kingston University was ideally placed to introduce, as part of its 1996 new curriculum, a Common Foundation Programme (CFP). This incorporated degree students in medicine, radiography, physiotherapy, and nursing learning togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
141
3
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(163 citation statements)
references
References 12 publications
15
141
3
2
Order By: Relevance
“…[40] Likewise, Tucker et al found that some students fear they do not have sufficient knowledge or competency to participate in shared learning. [41] Comparable to other findings, [18] the medical students in our study were younger (mean age 23.9) than nursing and physician associate students which may account for their feelings of awkwardness or embarrassment.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…[40] Likewise, Tucker et al found that some students fear they do not have sufficient knowledge or competency to participate in shared learning. [41] Comparable to other findings, [18] the medical students in our study were younger (mean age 23.9) than nursing and physician associate students which may account for their feelings of awkwardness or embarrassment.…”
Section: Discussionsupporting
confidence: 55%
“…[26] It has been suggested that negative perceptions of health professional students to their own and other professions may impact negatively on future work behaviors. [15] Research supports some health care students enter their educational programs with diverse attitudes and stereotypic views related to personal and professional culture and communication [15,18] and strongly identify with their own profession early on in their education. [19] These attitudes toward others may impact student's readiness toward shared team collaboration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Tunstall-Pedoe et al (2003) and Cooper et al (2005), students begin internalizing professional values upon matriculation, which may contribute to the various barriers experienced when practicing or learning within an interprofessional setting. Indeed, Rudland & Mires (2005) showed that first year medical students held negative stereotypes of their nursing colleagues even in the first week of classes.…”
Section: Practice Pointsmentioning
confidence: 99%
“…1 Research has also demonstrated that students embrace opportunities for IPE and reap benefits in the realms of knowledge, skills, and attitudes. 7,[11][12][13][14][15][16] Knowledge of a student's chosen profession has been shown to be strengthened by working with students of other professions as they explain, compare, and contrast their clinical skills. 12,17 Students have also been shown to benefit from collaborative patient care, which fosters the development of their professional roles 12,13 and bridges the gap between student and practising health care professional.…”
Section: Literature Reviewmentioning
confidence: 99%